IMPLEMENTASI VISUALISASI POLA KUNJUNGAN OBYEK WISATA DI BALI MENGGUNAKAN OPENSTREETMAP - Ida Ayu Gde Suwiprabayanti Putra; Luh Putu Safitri Pratiwi (Universitas Muhammadiyah Semarang, 2018)
Data on tourist visits released by the Bali Provincial Government Tourism Office shows that there are three most visited districts, namely Tabanan, Gianyar and Badung. There are differences in the number of very large visits with the other six districts. If this pattern continues, there is the possibility of boredom will be experienced by tourists and cause a decrease in visits to Bali. In previous studies, an analysis of the pattern of tourist attractions on the island of Bali was carried out. The algorithm used to analyze tourist visits is the Frequent Pattern Growth (FP-Growth) algorithm. After getting a visit pattern by using the Weka application, to show more results, in this study, the pattern will be visualized in the form of a website. The tourist location is visualized based on the website using OpenStreetMap. OpenStreetMap is a map built by conducting surveys using GPS, digitizing satellite imagery, and collecting and freeing geographic data available in the public. The Map Engine used to display OpenStreetMap is to use MapBox. The programming language used is Javascript and CSS. The recommendations are expected to help plan tourism packages in Bali for each district. Keywords: OpenStreetMap, Visualization, FP-Growth, Travel